(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. In the fourth technological revolution, the “fuel” for the economy is digitalization, not raw materials, so at each level, there are transformational processes associated with the introduction of new digital technologies, which are designed to change the mechanisms and quality of management, improve speed and efficiency access to information and knowledge base, change the algorithms of production processes, appropriate sales channels, etc. The purpose of the article. The purpose of the article is to analyze the transmission mechanism of the impact of digitalization of agricultural enterprises on the development of rural areas by describing the possible positive effects of digitalization in terms of the territorial community, rural population, and the state as a whole. Results. The transmission mechanism of the influence of digitalization of agricultural enterprises on the development of rural areas is substantiated. The possible effects of the digitalization of agricultural enterprises in the plane of economic, social, organizational, and technical-technological blocks are determined. The positive effects of the digitalization of agricultural enterprises in the context of groups of major external stakeholders are detailed: the territorial community, society, and the state. It is proved that the digitalization of agricultural enterprises will help to bridge the digital divide between rural areas in urban areas and increase the involvement of rural areas in the process of general digitalization. Conclusions. The digitalization of agricultural enterprises will have a synergistic impact on the development of rural areas. Facilitating and co-financing agricultural broadband in rural areas opens up new opportunities for its inhabitants on the road to a bright digital future and will help bridge the digital divide between cities and villages.